2009
DOI: 10.1093/rpd/ncp039
|View full text |Cite
|
Sign up to set email alerts
|

Neutron dose study with bubble detectors aboard the International Space Station as part of the Matroshka-R experiment

Abstract: As part of the Matroshka-R experiments, a spherical phantom and space bubble detectors (SBDs) were used on board the International Space Station to characterise the neutron radiation field. Seven experimental sessions with SBDs were carried out during expeditions ISS-13, ISS-14 and ISS-15. The detectors were positioned at various places throughout the Space Station, in order to determine dose variations with location and on/in the phantom in order to establish the relationship between the neutron dose measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…This result agrees well with the value (i.e. 66 %) provided by the SBDS, and with the earlier SPND data (6) collected using the same phantom during ISS-13 to ISS-19, which suggested a similar dose reduction inside the phantom.…”
Section: Bubble-detector Measurements: Iss-34 To Iss-37supporting
confidence: 92%
See 1 more Smart Citation
“…This result agrees well with the value (i.e. 66 %) provided by the SBDS, and with the earlier SPND data (6) collected using the same phantom during ISS-13 to ISS-19, which suggested a similar dose reduction inside the phantom.…”
Section: Bubble-detector Measurements: Iss-34 To Iss-37supporting
confidence: 92%
“…Experiments started in 2006 as part of the international Matroshka-R experiment based in the Russian segment of the ISS. Several measurements, each approximately a week long, were performed in the various Russian modules during the ISS-13 to ISS-19 missions (6,7) . This included experiments with the Matroshka-R tissueequivalent spherical phantom, which demonstrated that the dose received inside the phantom is lower than that at the phantom surface.…”
Section: Introductionmentioning
confidence: 99%
“…More recent accounts of neutron measurements made aboard the International Space Station are contained in several studies e.g. [21,25].…”
Section: Neutron Measurementsmentioning
confidence: 99%
“…Experiments and simulations have been conducted to explore the space radiation hazards that astronauts are exposed to. Experiments have been performed to measure the radiation doses received by humanlike phantoms including a phantom head (1989)(1990)), [1] a spherical phantom ), [2] the phantom torso 'Fred' (1998,2001), [3][4][5] and the MATROSHKA series of mannequins (MATROSHKA-R 2004-2005, [6][7][8] MATROSHKA-1 2004-2005, [9] MATROSHKA-2A 2005, [10] MATROSHKA-2B 2007, [10] and MATROSHKA-KIBO 2010-2011 [11] ) on board spacecraft. These human-like phantoms were well instrumented with radiation detectors in their vital organs so as to measure the biological radiation parameters, including the dose, the equivalent dose, the effective dose, etc.…”
Section: Introductionmentioning
confidence: 99%